2009
DOI: 10.1139/b08-139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of introduced Euphorbia esula on the pollination of Viola pedatifida

Abstract: Introduced plants may compete for pollination with native plants, resulting in reduced fruit or seed set. In this study, I use several techniques to assess whether the invasive plant Euphorbia esula L. (leafy spurge, Euphorbiaceae) reduces the pollination success of chasmogamous flowers of the native plant Viola pedatifida G. Don (prairie violet, Violaceae), which has chasmogamous and cleistogamous flowers. Euphorbia pollen was found on most Viola stigmas, suggesting the potential for competition. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…In contrast to other native-invasive plant pollinator interaction studies, where in-vasive plant species pollen is frequently found on the stigma of native plants (Brown et al 2002;Montgomery 2009aMontgomery , 2009b, almost no crown vetch pollen or any other heterospecific pollen grains were found on T. ohiensis. Morales and Traveset (2008) noted that low invasive pollen deposition on native stigmas in invaded areas could be more common than is assumed.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast to other native-invasive plant pollinator interaction studies, where in-vasive plant species pollen is frequently found on the stigma of native plants (Brown et al 2002;Montgomery 2009aMontgomery , 2009b, almost no crown vetch pollen or any other heterospecific pollen grains were found on T. ohiensis. Morales and Traveset (2008) noted that low invasive pollen deposition on native stigmas in invaded areas could be more common than is assumed.…”
Section: Discussioncontrasting
confidence: 89%
“…In the last decade, numerous studies (e.g., Larson et al 2006;Traveset and Richardson 2006 [and citations therein]; Nielsen et al 2008;Montgomery 2009aMontgomery , 2009bDietzsch et al 2011;Thijs et al 2012 [and citations therein]; Sun et al 2013) have addressed the question: Do invasive plant species compete with native plant species for pollinators? These studies have shown negative, positive, and neutral effects regarding the impact of invasive species on the reproduction of native species.…”
Section: Introductionmentioning
confidence: 99%
“…In many flowering plant communities multiple species bloom simultaneously and compete for the service of shared pollinators (Mitchell et al 2009). The consequences of competition for pollination have been well documented for species pairs (Waser 1978, Caruso 2000, Brown et al 2002, Montgomery 2009, Takakura et al 2009), but have received much less attention in more diverse plant communities (but see Ghazoul 2006, Lopezaria‐Mikel et al 2007, Lazaro et al 2009). Several studies of interspecific competition for abiotic resources have demonstrated that competitive outcomes may not be a simple additive function of pair‐wise interactions (Miller 1994, Dormann and Roxburgh 2005, Weigelt et al 2007, Perkins et al 2007).…”
mentioning
confidence: 99%
“…In contrast to manipulative experiments, observations of HP incidence under natural pollination regimes have revealed that quantities of HP received tend to be variable and from diverse donor species (Emer et al, 2015 ; Fang & Huang, 2013 ; Johnson & Ashman, 2019 ; Montgomery & Rathcke, 2012 ; Wei et al, 2021 ; Zhang et al, 2021 ). Consequently, effects may differ between manipulative studies and those investigating natural variation (e.g., Montgomery, 2009 ). Studies that evaluated the impact of natural HP receipt on plant reproduction in the field have observed no detrimental effect of HP (Montgomery, 2009 ), negative effects on conspecific pollen‐tube success (Parra‐Tabla et al, 2020 ), or negative interaction between conspecific pollen (CP) and HP quantities, with the effect of CP on seed production becoming weaker with larger quantities of HP deposition (Briggs et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, effects may differ between manipulative studies and those investigating natural variation (e.g., Montgomery, 2009 ). Studies that evaluated the impact of natural HP receipt on plant reproduction in the field have observed no detrimental effect of HP (Montgomery, 2009 ), negative effects on conspecific pollen‐tube success (Parra‐Tabla et al, 2020 ), or negative interaction between conspecific pollen (CP) and HP quantities, with the effect of CP on seed production becoming weaker with larger quantities of HP deposition (Briggs et al, 2016 ). Moreover, because the composition of co‐flowering species and pollinators can differ greatly across communities, different populations of the same species may receive HP from different donor species (Herrera, 1988 ; Johnson & Ashman, 2019 ), which suggests that the effects of HP receipt may vary among populations across a species' range.…”
Section: Introductionmentioning
confidence: 99%